A tuber ischium avulsion fracture treated with modified subgluteal approach: a case report - KÜÇÜKDURMAZ, FATİH; Saka, Gursel; KÜÇÜKDURMAZ, FATİH; Saglam, Necdet; Akpinar, Fuat (My University, 2012)
We report a 16-year-old soccer player with a displaced avulsion fracture of the ischial tuberosity sustained during a soccer match. Open reduction and internal fixation were performed using a longitudinal incision and subgluteal approach. The patient returned to sports 6 months following the operation and returned to his preoperative performance at the 16th month postoperative follow-up. Surgical treatment is often avoided for these types of fractures due to complications associated with the sciatic nerve and exposure difficulty. However, we believe that this incision is a safer alternative to existing methods, providing sufficient exposure and avoiding damage to the neurovascular structures. This article aims to review this alternative incision in the surgical treatment of avulsion fractures of the ischial tuberosity.
Keywords: case report